Translanguaging und sein Potenzial für den DaF-Unterricht sowie fachsprachlichen DaF-Unterricht - Saša Jazbec (Vestnik za Tuje Jezike)
Foreign language teaching, especially the teaching of non-English languages, is facing significant challenges today due to the status of English among languages and in the context of migration, globalization, and mediatization. The old, familiar methods that have long been successful with regard to language learning and teaching are now no longer effective, do not motivate learners, and do not achieve the results that teachers want. The current monolingual paradigm of foreign language teaching will thus have to change, and various different approaches are available. This paper focuses on translanguaging, a new approach to language processing and use that starts with the individual and their single linguistic repertoire.